The Compliance of Ship's Crew Toward International Convention Implementation for Controlling of Ballast Water and Sediment from Ships In Offshore Port of Taboneo - A Sulaiman; Achmad Syamsu Hidayat; Mijani Rahman; Noor Arida Fauzana (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
This study aims to analyze the level of compliance of the ship’s crew toward The BWM Convention. (Ballast Water Management Convetion). This research is kind of qualitative using a research design that relates the independent variables and the dependent variable at the same time. The study was conducted in the Offshore Port of Taboneo with a total sample of 54 respondents. The research data is primary data from interview by using questioner and secondary data obtained from interview and literature study. The results showed that the Compliance of the crew on the ship that has been equipped with Ballast Water Treatment System (BWTS) is 66.67 % of respondents fall into the category approach to obedient and 33.33 % of respondents approach to non-obedient category. So also the compliance of crew on board ship that has not been equipped with BWTS there are as many as 60.61 % of respondents fall into the category approach to obedient and 39.39 % of respondents approach to non-obedient category.